Uncertainty and contradiction: An essay on the business cycle - Michalis Nikiforos (Levy Economics Institute of Bard College, 2013)
This paper presents a discussion of the forces at play behind the economic fluctuations in the medium run and their relation with the short-run macroeconomic equilibrium. The business cycle is the result of two separate phenomena. On the one hand, there is the instability caused by the discrepancy between expected and realized outcomes. On the other hand, this instability is contained by the inherent contradictions of capitalism; the upswing carries within it the seeds of its own destruction. The same happens with the downswing. The paper provides a formal exposition of these insights, a discussion of how the formulation of this mechanism resembles the simple harmonic motion of classical mechanics, and an empirical evaluation.
Keywords: B22; E11; E12; E33; 330; Cycles; Harrod; Oscillations; Distribution